Treatment of a case with hysterical hearing loss - MN, Hegde; RK, Jagadeesh (Journal of All India Institute of Speech and Hearing, 1970)
Miss N., a 18 year old girl reported to the clinic on 4-7-69, with a comp- laint of hearing difficulty. She said she was experiencing great difficulty in hearing for the previous one month. The case came to the clinic alone and on further questioning she was unable to specify the exact time of onset. She felt that the problem could have been there even earlier but it was probably negligible. She also reported giddiness from the age of 8 years which was treated by several physicians but the case felt the treatment was ineffective.